Hypozincemia is associated with human hepatocarcinogenesis in hepatitis C virus‐related liver cirrhosis. Issue 10 (16th July 2019) - Shigefuku, Ryuta; Iwasa, Motoh; Katayama, Kazuhiro; Eguchi, Akiko; Kawaguchi, Takumi; Shiraishi, Koichi; Ito, Toshifumi; Suzuki, Kazutomo; Koreeda, Chizu; Ohtake, Takaaki; Tokumoto, Yoshio; Endo, Ryujin; et al.
Abstract : Aim: Hypozincemia is associated with the progression of chronic liver diseases, but it is unknown whether hypozincemia promotes human hepatocarcinogenesis. Our aim is to evaluate the serum zinc levels in liver cirrhosis (LC) patients and clarify the relationship between the serum zinc levels and the development of hepatocellular carcinoma (HCC). Methods: Cirrhotic patients without HCC ( n  = 299) were enrolled from 14 medical institutes in Japan as a multicenter prospective study (No. 2028). Of the 299 patients, 157 were included in the present study based on reliable and consistent serum zinc levels and no history of oral zinc supplementation. Clinical parameters associated with the development of HCC were determined. Furthermore, the cumulative incidence of HCC was analyzed using Kaplan–Meier methods and was calculated using the log–rank test. A Cox regression analysis was utilized for the multivariate analysis to evaluate the predictors of hepatocarcinogenesis. Results: Thirty of 157 patients (19.1%) developed HCC during an observation period of 3 years. Serum zinc levels were significantly decreased in hepatitis C virus‐related LC (C‐LC) patients with HCC (0.0180). The risk factors for incidence of HCC were hypozincemia (0.0014), high α‐fetoprotein (0.0080), low branched chain amino acids‐to‐tyrosine ratio (0.0128), or female sex (0.0228). Hypozincemia (hazard ratio 1.61, 0.0324) was the only significant predictor of hepatocarcinogenesis by multivariate Cox regression analysis. Conclusions: Hypozincemia is associated with hepatocarcinogenesis in C‐LC patients.